KEBERTAHANAN PASAR TRADISIONAL SAWAH LUNTO MENGHADAPI PANDEMI COVID-19 - Alimir Alimir; Fathur Rizqi; Redni Putri Meldianto (Turast: Jurnal Penelitian dan Pengabdian, 2022)
This research is a case study based on field research. The approach used in this study is a qualitative approach. The selection of informants is through a purposive sampling method, where the informants are selected based on certain criteria, including knowing the ins and outs of the research problem, so that in this study the most logical informants are economic actors consisting of sellers and buyers in the traditional markets of Sawahlunto. The number of informants in this study were 10 people consisting of 6 buyers and 4 sellers. Determination of the number of informants is based on snowball sampling, where when the data is considered saturated, the number of informants is considered sufficient to describe the actual situation. Observation and interview were chosen as data collection techniques. This article aims to describe the economic impacts faced by Sawahlunto Traditional Market traders due to the worldwide co-19 pandemic. The results of this study were during the covid-19 pandemic and the implementation of the Large-Scale Social Restrictions (PSBB), the traditional markets of Sawahlunto were significantly affected. The impact of PSBB was especially felt by traders of cloth, clothing, crockery, shoes, photocopying, and electronics stores. Another case with Gold Traders, despite a decline in transactions, world gold prices jumped sharply, so it is assumed that Gold Traders are still benefiting from this pandemic situation. In terms of gender, the number of male traders is more dominantly affected than female traders. The dominance of traders affected by the adam due to the majority of the economic sector which is engaged in daily commodities, such as food and spices are dominated by women, where the PSBB does not greatly affect the sale of daily goods, because these commodities are the most basic staples vital for the continuity of human life, and still needed whatever the circumstances and conditions that afflict humans.